2021
DOI: 10.3347/kjp.2021.59.4.363
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori GroEL Seropositivity Is Associated with an Increased Risk of Opisthorchis viverrini-Associated Hepatobiliary Abnormalities and Cholangiocarcinoma

Abstract: Despite the synergistic effect of Opisthorchis viverrini and Helicobacter pylori co-infection on pathogenesis of severe hepatobiliary abnormalities (HBA) including advanced periductal fibrosis and replace with cholangiocarcinoma (CCA) have been established, the immune response to H. pylori in O. viverrini infected population has never been explored. Hence, this study aimed to investigate the antibody responses to 2 immunogenic H. pylori proteins in O. viverrini-infected patients with HBA and CCA. The risk anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Opisthorchis viverrini infections lead to hepatobiliary manifestations, including advanced periductal fibrosis (APF), which is correlated with the risk of cholangiocarcinoma. The existing literature proposes that a carcinogenic bacterium, Helicobacter pylori ( H. pylori ), also contributes to the development of cholangiocarcinoma by enhancing the severity of hepatobiliary abnormalities [ 67 ]. A study by Hang et al found that even after completion of therapy with praziquantel, patients with co-infection by H. pylori , especially cagA-positive strain, continued to have persistent APF [ 68 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Opisthorchis viverrini infections lead to hepatobiliary manifestations, including advanced periductal fibrosis (APF), which is correlated with the risk of cholangiocarcinoma. The existing literature proposes that a carcinogenic bacterium, Helicobacter pylori ( H. pylori ), also contributes to the development of cholangiocarcinoma by enhancing the severity of hepatobiliary abnormalities [ 67 ]. A study by Hang et al found that even after completion of therapy with praziquantel, patients with co-infection by H. pylori , especially cagA-positive strain, continued to have persistent APF [ 68 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Intestinal helminthiases play a significant role in the observed undernutrition prevalence [9]. Furthermore, heavy and chronic infection with O. viverrini may cause severe hepatobiliary morbidity, including cholangiocarcinoma, a fatal bile cancer [15][16][17]. Severe hepato-splenic morbidity is associated to chronic S. mekongi infection.…”
Section: Introductionmentioning
confidence: 99%
“…Infection with O. viverrini is acquired through the consumption of traditional dishes prepared with raw or insu ciently cooked cyprinoid sh [20,21]. Heavy and chronic infection is associated with severe hepatobiliary morbidity, including the fatal bile duct cancer (cholangiocarcinoma) [22][23][24]. Today, small-scale studies of intervention using a chemotherapy-based approach have been conducted in the high endemic areas to explore the feasibility of control programs and provide evidence-based information for policy making and adaption.…”
Section: Introductionmentioning
confidence: 99%